Clinical study of the minimally invasive extraction of impacted supernumerary teeth in 85 cases - SONG Zhifeng; FEI Fei (口腔疾病防治, 2020)
Objective To explore the surgical design and surgical Methods for the minimally invasive extraction of embedded supernumerary teeth and to provide a reference for clinical practice. Methods A total of 87 embedded supernumerary teeth were removed from 85 patients. CBCT examination was performed before the operation. The nearest surgical approach was selected based on the distance between the embedded supernumerary teeth and the bony plate of the buccal tongue (lip and palate). The CBCT measuring ruler measured the maximum diameter of the impacted dental crown. According to the radius of the buccal and tongue directions of the crown, the upper and lower boundaries (bucco-lingual direction) of the bone to be deboned were determined with reference to the top of the alveolar crest or adjacent enamel cementum. A horizontal vertical line was made from the point to the meridian, and the length of the horizontal line was 1/2 the diameter of the impacted multiple crown. Thus, the radius determined the horizontal starting and ending points of the bone to be boneless. A trapezoidal or arcuate incision was made with an electric knife under block anesthesia and local infiltration anesthesia. The incision retained the gingival papilla. The upper and lower as well as the near and far midpoints of the bone were marked with a bone ruler. Starting from the midpoint area, the upper and lower points were connected. The mesial bone was removed in the mesial direction, and the range of the removed bone was slightly larger than the radius of the crown, showing the crown of the embedded supernumerary teeth. A surgical impact air handpiece with a 45-degree elevation angle or a piezosurgery device was used to divide the crown of the embedded supernumerary teeth into two parts. The crown and dental tissues were removed in pieces, the surgical area was cleaned and rinsed, and the wound was closed. Anti-inflammatory and swelling treatments were administered after the operation, and painkillers were prepared. The patients were revisited 7 days after the operation to check for wound healing. We asked and recorded the amount of painkillers taken by the patients. Results All patients had good wound healing 7 days after the operation, and the wounds were sutured. There was no swelling on the maxillofacial surface, and the degree of opening was basically normal. No other complications such as infection or numbness occurred. Fifty-eight patients did not take painkillers. Conclusion CBCT can be used to locate the embedded supernumerary teeth in bone. The surgical approach can be chosen based on the principle of proximity. During the surgery, the bone ruler is used to accurately locate the bone and remove the embedded supernumerary teeth in pieces, which can achieve a minimally invasive effect.